DESIGN OF A PC-BASED DC MOTOR SPEED CONTROLLER - Firas Mohammed Ali (Diyala Journal of Engineering Sciences, 2016)
This paper is concerned with the interfacing process between a personal computer and a permanent magnet DC motor. A practical interface circuit has been designed and implemented in order to control the speed of a permanent-magnet DC motor using a C++ control program.